HAK ATAS KESETARAAN DAN ANTI-DISKRIMINASI KELOMPOK IDENTITAS GENDER NETRAL (NON-BINARY) DALAM HUKUM POSITIF INDONESIA - Miftakhur Rohmah; Wiwik Afifah (Gapenas Publisher, 2023)
Knowledge about non-binary gender identity has become increasingly widespread over the past few years, but that does not mean that these groups are not discriminated and have received recognition in Indonesian positive law. The purpose of this article is to identify human rights violations by the state as a result of the lack of recognition of non-binary gender identity groups in Indonesian positive law. The research method used in making this scientific article is normative. The approach used is statute approach and comparison approach of Indonesian law with Australia and Argentina. The results of this study prove that there are human rights violations against non-binary gender identity groups by the state in the form of violations of the right to equality before the law and non-discrimination